(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the role of implementing the International Organization of Supreme Audit Institutions (INTOSAI) standards in improving financial performance quality, through a field study on the Libyan Audit Bureau. To achieve the study’s objectives, a descriptive-analytical approach was adopted, utilizing a questionnaire as the primary tool for data collection from auditors and financial experts within the Bureau, alongside analyzing audit reports and official publications issued by competent departments. The study revealed several key findings, most notably: there is a statistically significant impact of implementing INTOSAI standards on enhancing financial audit efficiency and improving performance quality indicators within audited entities, as compliance explains 51% of the variance in audit efficiency and 61% of the improvement in overall financial performance quality. Furthermore, the results showed that the Bureau’s commitment to international standards contributes to strengthening digital governance and mitigating operational and cyber risks arising from unofficial financial systems and fraudulent electronic applications (such as the "Ratibi" app) that threaten the integrity of state financial data and employee data privacy, which positively reflects on the sustainability and governance of funding allocated to developmental and sovereign sectors, including tourism and archaeology. The study recommended the necessity of expanding training programs for the Bureau’s auditing personnel on updated INTOSAI guidelines and developing audit mechanisms for electronic systems to ensure overall financial performance quality.